BUDIDAYA VERTIKULTUR DI PEKARANGAN SEBAGAI ALTERNATIF KETAHANAN PANGAN SAAT MASA PANDEMI BAGI MASYARAKAT PERUMAHAN (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2021)
Abstract. The Large-Scale Social Restrictions implemented to break the chain of the spread of COVID-19 have implications for the community's economy, for example, food compliance. To anticipate food scarcity on large scale, people can be educated to manage independent food gardens in organic vegetable gardens. The problem faced by people in urban areas is the unavailability of large areas for gardening. The solution that can be offered related to this condition is the application of technology by utilizing science and technology in the form of verticulture cultivation techniques in narrow land yards. This activity aims to apply verticulture technology that utilizes the capillary nature of water in the absorption of plant nutrients to facilitate partners who are generally housewives in maintaining and controlling plant nutrition until the harvest period. Partners in this community service are residents of the Tasikmalaya City of West Java, West Java, a resident of Perum Mitra Batik. The method used to apply technology is through extension activities in the form of lectures, discussions & questions and answers, training in the form of demonstration plots & planting practices on verticultural media, and supervision in the form of fertilization & plant maintenance until the harvest period. The results of the evaluation based on the indicators of the success of the activity showed that 90% of participants/partners admitted that they had increased knowledge about verticulture cultivation. 77.27% of participants/partners also feel very interested in doing verticulture cultivation in the future independently. Concern for the plants that have been planted is considered good, shown by the active role of participants/partners during the supervision and maintenance stages until harvest results are obtained that can be enjoyed by the community.       Abstrak. Pembatasan Sosial Berskala Besar (PSBB) yang dilaksanakan untuk memutus rantai penyebaran COVID-19 telah berimplikasi terhadap ekonomi masyarakat, salah satunya pemenuhan kebutuhan pangan. Demi mengantisipasi kelangkaan pangan dalam skala besar, masyarakat dapat diedukasi untuk mengelola kebun pangan mandiri berupa kebun sayuran organik. Permasalahan yang dihadapi oleh masyarakat di area perkotaan adalah tidak tersedianya area luas untuk berkebun. Solusi yang dapat ditawarkan terkait kondisi tersebut adalah penerapan teknologi tepat guna dengan memanfaatkan IPTEK berupa teknik budidaya vertikultur di pekarangan rumah berlahan sempit. Tujuan dari kegiatan ini adalah menerapkan teknologi vertikultur yang memanfaatkan sifat kapilaritas air dalam penyerapan nutrisi tanaman untuk memudahkan mitra yang umumnya ibu rumah tangga dalam perawatan dan kontrol nutrisi tanaman hingga masa panen. Mitra dalam pengabdian masyarakat ini adalah anggota KWT Rengganis dan anggota PKK RW 13 yang merupakan Warga Perum Mitra Batik Kota Tasikmalaya Jawa Barat. Metode yang dilakukan untuk menerapkan teknologi adalah dengan kegiatan penyuluhan berupa ceramah, diskusi & tanya-jawab, pelatihan berupa demplot & praktik tanam pada media vertikultur, serta pengawasan berupa pemupukan & pemeliharaan tanaman hingga masa panen. Hasil evaluasi berdasarkan indikator keberhasilan kegiatan menunjukkan 90% peserta/mitra mengaku mengalami peningkatan pengetahuan tentang budidaya vertikultur. 77,27% peserta/mitra juga merasa sangat tertarik untuk melakukan budidaya vertikultur pada masa mendatang secara mandiri. Kepedulian terhadap tanaman yang telah ditanam dinilai baik ditunjukkan dengan peran aktif peserta/mitra selama tahap pengawasan dan perawatan hingga diperoleh hasil panen yang dapat dinikmati oleh masyarakat.
Keywords: Food security; residential communities; verticulture cultivation